Pengaruh Digital Marketing Terhadap Keputusan Pembelian Pada Dealer Syariah Mobilindo Bogor - Fauzan, Rizky Muhammad; Mustikasari, Molly; Haryadi, Yudi (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
The rise of the digital era has made digital marketing strategies a vital component in influencing consumer behavior, including within the Sharia-compliant automotive sector. Dealer Syariah Mobilindo Bogor is one such business that has embraced digital approaches in its marketing activities. However, the effectiveness of these strategies on purchase decisions still requires academic investigation. This study aims to measure the impact of digital marketing on used car purchase decisions at Dealer Syariah Mobilindo Bogor. A quantitative approach was applied by distributing questionnaires to 156 respondents, and data were analyzed using SPSS version 27. The simple linear regression analysis resulted in the equation Y = 8.344 + 0.340X, with a regression coefficient of 0.340, indicating a positive effect. The t-value of 17.580 exceeds the t-table value of 1.975, and the significance level of 0.000 < 0.05 confirms statistical significance. The coefficient of determination (R² = 0.667) implies that 66.7% of the variation in purchase decisions is explained by digital marketing, while the correlation coefficient (Beta = 0.817) shows a strong positive relationship. The normality test also confirms that the data are normally distributed. The study concludes that a well-executed digital marketing strategy aligned with Sharia principles significantly influences consumer purchase decisions.